Respuesta :

Answer: A. (4,6)

Step-by-step explanation: 2(6y−4x = 20)                                                   3(−4y+3x = −12)                                                                                                     −8x+12y = 40                                                                                                     9x−12y = −36                                                                                                   -8x+9x                                                                                                                 +12y-12y                                                                                                               40-36                                                                                                                     x=4                                                                                                                   6y−4x = 20                                                                                                       6y−(4)(4) = 20                                                                                                   6y−16+16 = 20+16                                                                                                 6y/6 = 36/6                                                                                                           y = 6                                                                                                                       x = 4, and y = 6.

ACCESS MORE